Cinema Africa 24/25: A Conversation with Sana Na N’Hada, director of "Nome" (Cinema Africa 2024/25, 2026)
In his interview, director Sana Na N’Hada discusses his film Nome, presented at the Cinema Africa Festival 2024–2025 in Bayreuth. The conversation, conducted by festival organiser Prof. Dr. Ute Fendler and doctoral researcher Marie Tsogo, explores the film’s engagement with Guinea-Bissau’s struggle for independence, as well as its focus on memory, disillusionment and the complexities of post-revolutionary experience. N’Hada also reflects on his use of archival material and the personal and historical dimensions that shape the film. The interview was recorded as part of the 16th edition of the Cinema Africa Festival, curated by Prof. Dr. Ute Fendler and funded by the Africa Multiple Cluster of Excellence at the University of Bayreuth.